Konten Meme Marketing untuk Memitigasi Kelelahan Media Sosial dan Meningkatkan Niat Beli Generasi Z - Fadhil Adiyatma; Ratih Amelia (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to evaluate how meme marketing content influences social media fatigue and subsequent purchase intentions among Generation Z TikTok users in Indonesia. Utilizing a quantitative approach within a causal research design, data were gathered via a web-based questionnaire from 137 sampled individuals aged 17 to 25. The empirical data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) within the SmartPLS software environment. The findings revealed that meme marketing content exerts a significant negative effect on social media fatigue (β = −0.258, t = 3.832, p < 0.001), indicating that humorous marketing material effectively mitigates users' cognitive exhaustion. Furthermore, meme marketing content demonstrated a significant positive effect on purchase intention (β = 0.459, t = 5.318, p < 0.001). Conversely, social media fatigue showed neither a significant direct effect on purchase intention (β = −0.120, t = 1.532, p = 0.126) nor a significant mediating role between meme marketing content and purchase intention (β = 0.031, t = 1.267, p = 0.205). These findings suggest that meme marketing is an effective strategy to reduce digital fatigue while simultaneously driving purchase intentions among Generation Z consumers on TikTok